Perilaku Menyimpang (Studi Kasus Seksual Pranikah di Padangmawalle Kecamatan Tubbi Taramanu Kabupaten Polewali Mandar) - Ernianti Ernianti; Zainal Arifin (SOCIETIES: Journal of Social Sciences and Humanities, 2021)
Abstract. The purpose of this study is to describe deviant behavior (a case study of premarital sexual intercourse in Padangmawalle, Tubbi Taramanu District, Polewali Mandar Regency). This is a qualitative study with a descriptive approach. The technique in determining informants is snowball sampling, with the criteria of teenagers are those who are pregnant before marriage in the age of 11-25 years. There are 5 informants. Data collection techniques used are observation, interviews, and documentation. The data validity technique is using member check. Data analysis techniques were conducted in three stages; data reduction, data presentation, and drawing conclusion. The results of this study indicate that;  1) Factors causing premarital sexual intercourse of teenagers in Padangmawalle, Tubbi Taramanu District Polewali Mandar Regency are: Internal Factors: a) teenagers' lack of knowledge about sex, sexual, and sexuality. External factors: a) social media (youtube, facebook, and whatsapp) (b) The lack of sex education by parent towards children. (c) The influence of teenagers peer. 2) The impact of premarital sexual intercourse on teenagers in Padangmawalle, Tubbi Taramanu District, Polewali Mandar Regency are: a) Psychological impacts (feeling worried, frustrated, anxious, and guilty for what was done).  and b) Social impacts (exclusion, dropping out of school, and being the topic of conversation among people). Keywords: Deviant behavior, premarital sexual intercourse, teenagers.